On Intertextual Relations of Two Novels: G. Markosyan- Kasper's "Penelope" and B. Vian's "Froth on the Daydream" - AVETISYAN, VENERA (Bulletin of Yerevan University H: Russian Philology, 2021)
Тhe author gives in this article a comparative analysis of two novels – "Froth on the Daydream" of Boris Vian and "Penelope" of Gohar Markosyan-Kasper. Based on the intertextual link, the line from Vian to Markosyan-Kasper is traced, from the French avant-garde with elements of the absurd theater of the 40s to the post-Soviet "myth", which in turn refers to the antique. However, Vian's "Froth on the Daydream" is just one of the many intertextual layers of the novel "Penelope", and the Vian’s stile and moods that form a certain atmosphere are transformed and presented here in a different vein.
Keywords: intertextuality,theater of the absurd, a turning point, post-Soviet myth